1992
DOI: 10.1063/1.352256
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of oxide precipitates in Czochralski silicon degenerately doped with boron

Abstract: Articles you may be interested inEffect of heavy boron doping on the lattice strain around platelet oxide precipitates in Czochralski silicon wafers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…tion was enhanced in the heavily boron-doped specimen. Thus, for the specimen H1, with the enhancements of the grown-in oxygen precipitates during crystal growth by boron doping [10,16] and the injection of vacancy to the bulk during RTA pre-annealing process [16,17], oxygen precipitates with high density generated in the bulk, as shown in Figs. 1 and 3, respectively.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…tion was enhanced in the heavily boron-doped specimen. Thus, for the specimen H1, with the enhancements of the grown-in oxygen precipitates during crystal growth by boron doping [10,16] and the injection of vacancy to the bulk during RTA pre-annealing process [16,17], oxygen precipitates with high density generated in the bulk, as shown in Figs. 1 and 3, respectively.…”
Section: Resultsmentioning
confidence: 88%
“…It is believed that high concentration boron atoms may react with oxygen to form a large amount of boron-oxygen complexes, which can provide the heterogeneous nuclei center for oxygen precipitation. It is also reported that the degenerately doping with boron could lower the elastic moduli of silicon in both [1 1 0] and [1 1 1] direction and therefore the lattice strain introduced by the oxygen precipitates [10]. Thus, there is no doubt that compared with that of the lightly boron-doped specimen, the oxygen precipita- Fig.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Third, the yield strength of silicon crystal decreases significantly with increasing temperature, leading to much easier generation of dislocations at higher temperature. 19 In view of the abovementioned analyses, it is clear that at higher temperature extended defects can be generated by relatively smaller-sized oxygen precipitates. Figure 5 shows the change in critical size for the generation of extended defects with the annealing ambient (N 2 , Ar, and O 2 ) for specimens annealed at 1050°C for 32 h. Here, the critical sizes for each specimen were also derived from the BMD size profiles measured at ten positions.…”
Section: Resultsmentioning
confidence: 98%